Eosinophilic Pustular Folliculitis of Infancy: A Histologic Assessment of 43 Cases. (5th June 2022) - Fertitta, Laura; Bodemer, Christine; Molina, Thierry; Frassati-Biaggi, Annonciade; Fraitag, Sylvie; Leclerc-Mercier, Stéphanie
Abstract: Eosinophilic pustular folliculitis of infancy is a sterile, inflammatory dermatosis that mainly affects children younger than 36 months. The underlying physiopathologic mechanism is unclear. Clinical diagnosis is challenging, and a skin biopsy may be necessary. The literature data are sometimes contradictory, and a histologic series of eosinophilic pustular folliculitis of infancy cases has not been previously published.